Library acquisition policies and procedures - Futas, Elizabeth (Phoenix, Arizona : Oryx Press, 1977)
Library Acquisition Policies and Procedures is designed to aid librarians, library school students and publishers to understand some of the factors which underlie and influence library materials selection.
Public Library policies -- Academic Library Policies -- Partial Library Policies by Category.
Includes bibliographical references and index.
Keywords: LIBRARY MANAGEMENT